2020
DOI: 10.3390/insects11110783
|View full text |Cite
|
Sign up to set email alerts
|

Colony-Level Effects of Amygdalin on Honeybees and Their Microbes

Abstract: Amygdalin, a cyanogenic glycoside, is found in the nectar and pollen of almond trees, as well as in a variety of other crops, such as cherries, nectarines, apples and others. It is inevitable that western honeybees (Apis mellifera) consistently consume amygdalin during almond pollination season because almond crops are almost exclusively pollinated by honeybees. This study tests the effects of a field-relevant concentration of amygdalin on honeybee microbes and the activities of key honeybee genes. We executed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 89 publications
2
15
0
Order By: Relevance
“…Microbe counting using NGS reads essentially followed (Tauber et al, 2020), which contains a detailed workflow and command lines: demultiplexed and trimmed files were run in fastp for quality control (Chen et al, 2018), Hisat2 to remove honeybee reads (Kim et al, 2019), files manipulated using samtools (Li et al, 2009), Kraken2 to count microbe‐derived reads (using only paired reads) (Wood et al, 2019), and correction of counts with Bracken (Lu et al, 2017). The Confidence score for the Kraken2 algorithm was increased to 0.1 for this work.…”
Section: Methodsmentioning
confidence: 99%
“…Microbe counting using NGS reads essentially followed (Tauber et al, 2020), which contains a detailed workflow and command lines: demultiplexed and trimmed files were run in fastp for quality control (Chen et al, 2018), Hisat2 to remove honeybee reads (Kim et al, 2019), files manipulated using samtools (Li et al, 2009), Kraken2 to count microbe‐derived reads (using only paired reads) (Wood et al, 2019), and correction of counts with Bracken (Lu et al, 2017). The Confidence score for the Kraken2 algorithm was increased to 0.1 for this work.…”
Section: Methodsmentioning
confidence: 99%
“…Although bees and their native microbiota seem to tolerate relatively high doses of amygdalin, parasites that commonly inhabit the bee gut may not fare as well. There is increasing evidence that metabolites in nectar and pollen, even those considered toxic in some cases, can improve pollinator health at specific concentrations by controlling or reducing parasite loads (16,29,(50)(51)(52). Indeed, bees tend to forage on specific plants as a means of reducing colony pathogen loads (51).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, bees tend to forage on specific plants as a means of reducing colony pathogen loads (51). For example, honey bees from hives treated with amygdalin exhibited decreased levels of infection by the parasite Lotmaria passim and some viruses (29). In contrast, this does not seem to be the case for Crithidia infection in bumble bees, whose loads are not reduced after amygdalin exposure (53), as the parasite is not susceptible to amygdalin (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have looked for effects of phytochemicals on immune gene expression have generally found them, though nearly all such studies have used the western honey bee ( Boncristiani et al, 2012 ; Lu et al, 2020 ; Mao et al, 2013 ; Palmer-Young et al, 2017c ). Compound classes that influence immune gene regulation include alkaloids ( Lu et al, 2020 ; Palmer-Young et al, 2017c ), terpenoids ( Boncristiani et al, 2012 ; Palmer-Young et al, 2017c ), phenolic acids ( Mao et al, 2013 ; Palmer-Young et al, 2017c ), and iridoid glycosides ( Palmer-Young et al, 2017c ), with two studies finding no effect of the cyanogenic glycoside amygdalin on AMP expression ( Palmer-Young et al, 2017c ; Tauber et al, 2020 ). Most studies document a positive relationship between phytochemical consumption and immune gene expression ( Lu et al, 2020 ; Mao et al, 2013 ; Palmer-Young et al, 2017c ), suggesting an immune-boosting effect of phytochemical consumption, but Boncristiani et al (2012) found that thymol exposure downregulated immune recognition and signaling, although AMP production was unaffected.…”
Section: Host-mediated Effectsmentioning
confidence: 99%